The cork viewed from the inside - Lagorce-Tachon, Aurélie; Karbowiak, Thomas; Loupiac, Camille; Gaudry, Alexandre; Ott, Frédéric; Alba-Simionesco, Christiane; Gougeon, Régis D.; Alcantara, Valentin; Mannes, David; Kaestner, Anders; Lehmann, Eberhard; Bellat, Jean-Pierre (Journal of Food Engineering, 2015)
Cork is the natural material stripped from the outer bark of cork oak. It is still the most used stopper to seal wine bottles and to preserve wine during storage. Cork stoppers are sorted in different classes according to apparent defects, named lenticels, which can be related to the cork macroporosity. The more lenticels there are, the worst cork quality is. The present work aims at investigating defects analysis of cork stoppers from two classes by comparing digital photography and neutron imaging. Surface analysis of defects obtained from photography leads to more surface defects in class 4 (6.7%) than in class 0 (4.1%). Neutron radiography and tomography are powerful methods that really show the defects inside the material. From neutron radiography and tomography, class 0 contains 5.4% of volume defects and class 4 6.5%. Moreover, tomography also allows observing defects distribution along the whole stopper and possible interconnectivity.
Keywords: Cork; defect detection; image analysis; neutron imaging; Porosity; tomography

Adsorption equilibria of water vapor on cork. - Lequin, Sonia; Chassagne, David; Karbowiak, Thomas; Gougeon, Régis; Brachais, Laurent; Bellat, Jean-Pierre (Journal of agricultural and food chemistry, 2010)
We report here for the first time a complete thermodynamic study of water vapor adsorption on crude cork powder and plate. Adsorption-desorption isotherms were accurately measured by thermogravimetry at 283, 298, and 313 K in a large range of relative pressure. Adsorption enthalpies were determined by calorimetry as a function of loading. Adsorption-desorption isotherms exhibit a hysteresis due to the swelling of the material. The influence of the presence of lenticels on the adsorption properties of cork is found to be negligible. A detailed analysis and interpretation of adsorption data allow proposal of an adsorption mechanism in two steps. (i) First, water adsorbs on hydrophilic sites constituted by hydroxyl and methoxyl groups. (ii) Then water adsorption continues by clusters formation around the hydrophilic sites.
The following values have no corresponding Zotero field: accession-num: 20192215
Keywords: Adsorption; Plant Bark; Plant Bark: chemistry; Quercus; Quercus: chemistry; Thermodynamics; water; Water: chemistry